1976
DOI: 10.1111/j.1432-1033.1976.tb10043.x
|View full text |Cite
|
Sign up to set email alerts
|

An Intracellular Endonuclease of Bacillus subtilis Specific for Single‐Stranded DNA

Abstract: We have fractionated from extracts of Bacillus subtilis the DNase activity specific for singlestranded DNA; the activity separates in two main fractions on Sephadex G-200, a larger one ( M , > 400000) and a smaller one ( M , z 30000). We have purified the smaller, more abundant fraction nearly 3000-fold. The purified enzyme has a pH optimum close to 8, is activated by Ca", and is inhibited by EDTA ; the enzyme hydrolyses single-stranded DNA at a rate approximately 40 times greater than double-stranded DNA. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
8
1

Year Published

1977
1977
2018
2018

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 21 publications
0
8
1
Order By: Relevance
“…Some of the enzymes have been implicated in the process of recombination, e.g. an ATP-dependent DNAase (Chestukhin et al, 1972;Doly & Anagnostopoulos, 1976) and an endonuclease specific for single-stranded DNA (Ciarrocchi et al, 1976). It was reported that mutants that were inhibited in recombination also possessed lower activities of these enzymes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Some of the enzymes have been implicated in the process of recombination, e.g. an ATP-dependent DNAase (Chestukhin et al, 1972;Doly & Anagnostopoulos, 1976) and an endonuclease specific for single-stranded DNA (Ciarrocchi et al, 1976). It was reported that mutants that were inhibited in recombination also possessed lower activities of these enzymes.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly the heat-activated endonuclease (Burke & Spizizen, 1977) can hydrolyse native or denatured DNA, but also does not degrade the DNA to acid-soluble material. Apart from the endonuclease specific for single-stranded DNA (Ciarrocchi et al, 1976), most of the remaining well-characterized DNAases of B. subtilis are exonucleases (Kerr et al, 1965;Okazaki et al, 1966;Kanamori et al, 1974).…”
Section: Discussionmentioning
confidence: 99%
“…The moving terrestrial/aquatic transition creates a great variety of environmental conditions conducive to biodiversity, whereas during high water period primary productivity is weaker because of dilution, shorter residence time, and increased depth (Ciarrocchi et al, 1976;Scho ngart & Junk, 2007;Thomaz et al, 2007;Junk et al, 2012). During the flushing period, decreasing depth and degradation of the autogenic organic material pro-motes a second peak in primary productivity (Ciarrocchi et al, 1976;Alcântara et al, 2011). During low water, floodplains present a smaller water volume profoundly stirred and turbid and remain or not connected to the main channel (Tockner et al, 2000).…”
Section: Introductionmentioning
confidence: 99%
“…Protoplasts were suspended in 3 ml of 0.01 M Tris-hydrochloride buffer (pH 7.5), 1 mM dithiothreitol, and 1 mM CaCl2 and sonicated for 5 s at 0°C. The DNase activity was assayed using methods previously described (3). DNA polymerase I (Pol I) activity, defined as thep-chloromercuribenzoate-insensitive fraction of the total DNA polymerase activity, was assayed by the method of Ciarrocchi et al (2).…”
mentioning
confidence: 99%